Board of director's characteristics and the likelihood of corporate fraud: Malaysian case / Airul Aezza Kamaruzzaman - Kamaruzzaman, Airul Aezza (2013)
This research investigates whether the board of director's characteristics, i.e. board size, board meeting, board ethnicity, board gender diversity, board independence, and chairman dual role, are associated with the likelihood of fraudulent financial reporting. The sample of this study includes all fraud firms which has been disclosed by the Securities Commission Malaysia matched with an equal number non-fraud firm. A total of 124 firms are included in this study, consisting 62 firms that engaged in fraudulent financial reporting and other 62 of non-fraud firms. Using the logistic regression analysis, the findings show that there is significant relationship between board characteristics (board size, board meeting, board ethnicity, board independence, and chairman dual role) and fraudulent financial reporting. Specifically, the result shows that fraudulent financial reporting is positively associated with board size. In addition, the result shows that firms engaging with fraud have more frequent board meeting, is dominated by Chinese ethnicity, have high proportion of independent directors and the chairman and Chief Executives Officer (CEO) or Managing Director are the same person/director. Overall, this research contributes new evidence on the factors that explain the likelihood of fraudulent financial reporting.